Environmental and individual factors associated with protection and predisposition to autoimmune diseases - Júnior, Dilceu Silveira Tolentino (International Journal of Health Sciences, 2020)
Objective: This study aimed to correlate possible predisposing and protective factors involved with autoimmune diseases (ADs) in a Brazilian microregion. Methods: This case-control study recorded 362 cases of ADs prevalent in the Águas Formosas microregion, state of Minas Gerais, Brazil, between January and December 2016, through the application of a questionnaire. Overall, 724 controls were randomly selected according to gender and age. Logistic regression was used to calculate the adjusted odds ratio (OR), confidence interval, and P-value to compare the strength of association between the variables of interest assessed. Results: Individuals with Graves’ disease (OR: 11.9977), followed by rheumatoid arthritis (RA), psoriasis, lupus, Hashimoto’s thyroiditis (HT), and vitiligo, were strongly associated with the risk of developing the disease after the hepatitis B vaccine. Having consumed cow milk before 6 months of life was a factor associated only with psoriasis (OR: 0.3321) and RA (OR: 0.2880). Type 1 diabetes patients were associated only with surgical procedures (OR: 0.1160), just as physical and psychological traumas were associated only with vitiligo (OR: 5.9848). Contact with chemicals was more related to vitiligo (OR: 0.7142), RA, psoriasis, lupus, and thyroiditis. Physical exercise was the most significant protective factor for vitiligo (OR: 0.4904), followed by HT, RA, psoriasis, and lupus; and the consumption of filtered water with candles was a protective factor for vitiligo (OR: 0.3325). Conclusion: The associations suggest that predisposing and protective factors for ADs play a pivotal role in their onset, enabling health management, control, and intervention of this population.